Obesity does not modify the effect of continuous positive airway pressure on insulin resistance in adults with obstructive sleep apnoea. Issue 2 (13th March 2023) - Pak, Victoria M.; Maislin, David G.; Keenan, Brendan T.; Guo, Xiaofeng; Townsend, Ray; Benediktsdottir, Bryndis; Pack, Allan I.; Gislason, Thorarinn; Kuna, Samuel T.
Obstructive sleep apnoea (OSA) and obesity are independent risk factors for the development of insulin resistance [1]. Studies on the impact of continuous positive airway pressure (CPAP) treatment on insulin resistance [2] have shown the CPAP significantly improved insulin resistance based on the Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) values in patients with type 2 diabetes and OSA. However, the effect of obesity on the insulin resistance response to CPAP treatment of adults with OSA is unknown. The goal of this study was to compare the changes in HOMA-IR following 4 months adherence to CPAP treatment in obese and non-obese adults with OSA. We postulated that HOMA-IR would improve with the reversal of OSA pathophysiology caused by adherence to CPAP treatment, and that the benefits of CPAP would differ in obese and non-obese individuals. This study found no evidence that obesity significantly modifies the effect of 4 months of CPAP treatment on HOMA-IR. Longer duration of CPAP treatment may be needed in order to reduce insulin resistance and determine whether obesity modifies the effect. https://bit.ly/3CtX7jZ